Explanation of inconsistencies in the determination of human serum albumin thermal stability - Nemergut, Michal; Sedláková, Dagmar; Fabriciová, Gabriela; Belej, Dominik; Jancura, Daniel; Sedlák, Erik (International journal of biological macromolecules, 2023)
Thermal denaturation of human serum albumin has been the subject of many studies in recent decades, but the results of these studies are often conflicting and inconclusive. To clarify this, we combined different spectroscopic and calorimetric techniques and performed an in-depth analysis of the structural changes that occur during the thermal unfolding of different conformational forms of human serum albumin. Our results showed that the inconsistency of the results in the literature is related to the different quality of samples in different batches, methodological approaches and experimental conditions used in the studies. We confirmed that the presence of fatty acids (FAs) causes a more complex process of the thermal denaturation of human serum albumin. While the unfolding pathway of human serum albumin without FAs can be described by a two-step model, consisting of subsequent reversible and irreversible transitions, the thermal denaturation of human serum albumin with FAs appears to be a three-step process, consisting of a reversible step followed by two consecutive irreversible transitions. •Thermal stability of albumin samples varies from batch to batch.•Thermal denaturation of albumin is a kinetically controlled multi-step process.•The presence of FAs causes a more complex thermal denaturation of albumin.•The thermal stability of albumin is strongly pH-dependent, even within a single conformational form.